Business plan: MBizM Group focussing on branding, digital marketing & product innovation - Rendhawa, Dhalita (2019)
This paper provides a strategic business overview of the MBizM Group, a Lean Six Sigma (LSS) training and consultancy group of companies, that have been in operations in the Malaysian market for 10 years. Despite having paid little or no attention to branding and marketing activities, MBizM’s Company Directors, driven by the passion to embed LSS ‘The Right Way’ have, over the years, successfully built a business with group revenues exceeding RM 1.5 Million. Keen to propel MBizM group into the RM 2-2.5 Million revenue bracket and position MBizM as Malaysia’s ‘One-stop Shop’ for LSS; this paper focuses on four things: